UAVs assisted queue scheduling in ground ad hoc networks. (2019) - Sharma, Vishal; Kumar, Rajesh
Hybrid networks provide a vast range of applications in areas of military and civilian activities. One of the examples of hybrid network formations is unmanned aerial vehicles (UAVs) assisted ground ad hoc networks. Efficient coordination in these networks can resolve complex issues such as coverage, proper connectivity, scalability, and QoS. However, reliable data transmission with enhanced QoS is one of the key challenges in these types of hybrid ad hoc formations. In this paper, an efficient queue scheduling approach is proposed that allows improved QoS to end users. The proposed queue scheduling approach is developed in two parts. The first part utilises the Quaternion based Kalman Filter to find the appropriate locations for placement of each UAV. In the second part, satisfied importance analysis (SIA) is used to find the governing rules for the selection of appropriate queue for transmission. The effectiveness of the proposed model is demonstrated using simulations.